PERANCANGAN SISTEM INFORMASI PERSEDIAAN SUKU CADANG PESAWAT PADA PT PRAKARSA MULTISARI MANDIRI JAKARTA - Setiabudi, Arifin; Masria, Masria (POLITEKNIK LP3I JAKARTA, 2019)
PT Prakarsa Multisari Mandiri is a company engaged in the aviation sector located at The Garden Center Floor 5 Unit 22, Jakarta. This company still needs the right data processing in order to create time efficiency and data accuracy that can support operational, management and decision-making processes properly and accurately. In the case of inventories, this company still does not use a computerized system, employees within the warehouse scope are still recording manually after printing the form created using Microsoft Excel and then the data is stored back into the computer. Keywords: Aircraft Spare Parts Inventory, Spare Parts, Aircraft, Excel.